2017
DOI: 10.1097/md.0000000000006351
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA-related gene XPO5 rs11077 polymorphism with susceptibility to thyroid cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…As XPO5 is a key factor for the transportation of miRNA from the nucleolus, it has been postulated as a rate-limiting step in the development of miRNAs, so its impairment could lead to pre-miRNA trapping in the nucleolus, influencing the risk of cancer [60][61]. Current studies have indicated the role of XPO5 in the development of several sorts of cancers such as hepatocellular carcinoma, thyroid cancer, lung cancer, and so on [62][63][64]. These studies are consistent with the results of the present study in which XPO5 mRNA expression levels were significantly increased in tumor tissues compared to normal tissues in 154 paired cancer tissue samples from the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…As XPO5 is a key factor for the transportation of miRNA from the nucleolus, it has been postulated as a rate-limiting step in the development of miRNAs, so its impairment could lead to pre-miRNA trapping in the nucleolus, influencing the risk of cancer [60][61]. Current studies have indicated the role of XPO5 in the development of several sorts of cancers such as hepatocellular carcinoma, thyroid cancer, lung cancer, and so on [62][63][64]. These studies are consistent with the results of the present study in which XPO5 mRNA expression levels were significantly increased in tumor tissues compared to normal tissues in 154 paired cancer tissue samples from the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…The XPO5 gene has been found to play a role in carcinogenesis, as it was reported that certain cancers (e.g., non-small-cell lung cancer, esophageal squamous cell carcinoma, gastric cancer, hepatocellular carcinoma, and thyroid cancer) express levels of XPO5 that are distinct from those detected in normal cells [43,44,45,46,47,48]. In particular, a number of studies have reported that XPO5 polymorphisms at the rs11077 locus affect disease development and patient survival in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the XPO5 miRNA-SNP, rs11077, is a potential biomarker for thyroid cancer prediction, via its functional impact upon XPO5 expression [65]; however, there is no report of a functional connection between XPO5 and thyroid cancer incidence.…”
Section: Significance Of Microrna Polymorphisms In Nmtcmentioning
confidence: 99%